APPROACHES TO IMPROVING THE METHODS OF EVALUATING THE EFFECTIVENESS OF CORPORATE MANAGEMENT IN JOINT-STOCK COMMERCIAL BANKS (American Journal of Interdisciplinary Research and Development, 2023)
This article discusses the concept of the effectiveness of corporate governance and the model for determining the effectiveness of corporate governance, proposed by foreign and international organizations (OECD), as well as the main indicators characterizing the effectiveness and methodology for determining the effectiveness of corporate governance. The author's approach is formulated to determine the effectiveness of corporate governance and key performance indicators.